2006
DOI: 10.1101/gad.1458906
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ablation of ILK from the murine heart results in dilated cardiomyopathy and spontaneous heart failure

Abstract: A requirement for integrin-mediated adhesion in cardiac physiology is revealed through targeted deletion of integrin-associated genes in the murine heart. Here we show that targeted ablation of the integrin-linked kinase (ILK) expression results in spontaneous cardiomyopathy and heart failure by 6 wk of age. Deletion of ILK results in disaggregation of cardiomyocytes, associated with disruption of adhesion signaling through the ␤1-integrin/FAK (focal adhesion kinase) complex. Importantly, the loss of ILK is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(167 citation statements)
references
References 34 publications
12
151
4
Order By: Relevance
“…We assessed the effects of cardiac Gab1 deletion on Gab1 downstream signaling in hearts of Gab1-cKO and Gab1-WT control mice after 2 weeks of TAC or sham operation. In agreement with previous studies, [28][29][30] TAC increased ERK1/2 phosphorylation in Gab1-WT mice compared with sham control, but this response was impaired in Gab1-cKO mice (Figures 3a and b). TAC also induced p38MAPK phosphorylation in Gab1-WT mice, and this TAC-induced phosphorylation of p38MAPK was further enhanced in Gab1-cKO mice.…”
Section: Resultssupporting
confidence: 93%
“…We assessed the effects of cardiac Gab1 deletion on Gab1 downstream signaling in hearts of Gab1-cKO and Gab1-WT control mice after 2 weeks of TAC or sham operation. In agreement with previous studies, [28][29][30] TAC increased ERK1/2 phosphorylation in Gab1-WT mice compared with sham control, but this response was impaired in Gab1-cKO mice (Figures 3a and b). TAC also induced p38MAPK phosphorylation in Gab1-WT mice, and this TAC-induced phosphorylation of p38MAPK was further enhanced in Gab1-cKO mice.…”
Section: Resultssupporting
confidence: 93%
“…6, this kinase coordinates cues from ECM, including distinct signal inputs from integrins and growth factor receptor tyrosine kinases. This signaling was shown to regulate the cellular structural integrity and homeostasis in skeletal and cardiac muscle (31,32). The inactivation of ILK results in the loss of structural integrity in cardiac muscle (32), while it does lead to the development of a mild progressive muscular dystrophy, characterized by extensive fibrosis and irregular fiber size with centralized nuclei in skeletal muscle (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…8 All procedures followed National Institutes of Health guidelines and were approved by the Animal Research Ethics Committee of the Montreal Heart Institute. Studies were performed in 5-and 10-week-old mice, as well as age-matched controls, as indicated.…”
Section: Animal Modelmentioning
confidence: 99%
“…8 Phenotypic characterization has been limited: increased mortality, cardiac hypertrophy, ventricular dilation, and reduced LVEF were described in mice with targeted ILK deletion, 8 whereas reduced integrin-binding capacity and loss of endothelial cells were reported with clinical ILK mutationassociated DCM. 9 This study constitutes the first detailed phenotypic characterization of the cardiomyopathy caused by ILK deletion.…”
Section: Ilk-dysfunction Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation